Analysis of 23 Years of Daily Cloud-Free Chlorophyll and Suspended Particulate Matter in the Greater North Sea - Alvera-Azcárate, Aida; Van der Zande, Dimitry; Barth, Alexander; Troupin, Charles; Martin, Samuel; Beckers, Jean-Marie (Frontiers in Marine Science, 2021)
Satellite-derived estimates of ocean colour variables are available for several decades now and allow performing studies of the long-term changes occurred in an ecosystem. A daily, gap-free analysis of chlorophyll (CHL) and suspended particulate matter (SPM) at 1~km resolution over the Greater North Sea during the period 1998-2020 is presented. Interannual changes are described, with maximum average CHL values increasing during the period 1998-2008, a slightly decreasing trend in 2009-2017 and an stagnation in recent years. The typical spring bloom is observed to happen earlier each year, with about 1 month difference between 1998 and 2020. The duration of the bloom (time between onset and offset) has also increased with time, but the average CHL value during the spring bloom does not show a clear trend. The causes for earlier spring blooms are still unclear, although a rising water temperature can partially explain them. SPM values during winter months (prior to the development of the spring bloom) do not exhibit a clear trend over the same period, although slightly higher SPM values are observed in recent years. The influence of sea surface temperature in the spring bloom timing is therefore dominant over the influence of SPM concentration, according to our results. The number of satellites available over the years for producing CHL and SPM in this work has an influence in the total amount of available data before interpolation. The amount of missing data has an influence in the total variability that is retained in the final dataset, and our results suggest that at least three satellites would be needed for a good representation of ocean colour variability.